2015
DOI: 10.1016/j.neurobiolaging.2014.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Association of CD33 polymorphism rs3865444 with Alzheimer's disease pathology and CD33 expression in human cerebral cortex

Abstract: Recent findings identified the minor A allele present in the single nucleotide polymorphism rs3865444 in the CD33 gene as being associated with reduced risk of developing Alzheimer’s disease (AD). CD33 (Siglec-3) is an immune function protein with anti-inflammatory signaling, cell adhesion and endocytosis functions with sialic acid-modified proteins or lipids as ligands. Its involvement in AD pathological mechanisms is still unclear, so the goal of this study was to investigate if the rs3865444 polymorphism af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
82
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(84 citation statements)
references
References 61 publications
2
82
0
Order By: Relevance
“…The CD33 SNP rs3865444 C was associated with increased CD33 expression, leading to an accumulation of amyloid pathology as measured by Pittsburgh compound B (PiB) positive imaging signal [73]. This is in agreement with the finding that increased expression of CD33 mRNA was associated with accelerating AD pathology in cortical brain samples [74]. By contrast, another study reported reduced CD33 expression in CD33 SNP rs3865444 carriers [75], but CD33 inactivation promoted Ab uptake by microglia and mitigated Ab plaque deposition in CD33 knockout animals when crossed with an APP transgenic mouse [75].…”
Section: Microglia and Myeloid Cells During Adsupporting
confidence: 85%
“…The CD33 SNP rs3865444 C was associated with increased CD33 expression, leading to an accumulation of amyloid pathology as measured by Pittsburgh compound B (PiB) positive imaging signal [73]. This is in agreement with the finding that increased expression of CD33 mRNA was associated with accelerating AD pathology in cortical brain samples [74]. By contrast, another study reported reduced CD33 expression in CD33 SNP rs3865444 carriers [75], but CD33 inactivation promoted Ab uptake by microglia and mitigated Ab plaque deposition in CD33 knockout animals when crossed with an APP transgenic mouse [75].…”
Section: Microglia and Myeloid Cells During Adsupporting
confidence: 85%
“…Several genome-wide association studies found that alleles of CD33 influence the risk of late-onset Alzheimer's disease (LOAD) (7)(8)(9)(10). LOAD is a human disease that impairs the cognitive function of post-reproductive individuals, and other primates do not appear to be susceptible (11)(12)(13).…”
mentioning
confidence: 99%
“…One integrative functional genomics report followed up on the immune system gene CD33 , which was previously implicated in AD through GWAS [113, 114], by demonstrating SNP-associated changes in CD33 expression (protein), phagocytic performance of CD33-expressing monocytes (cellular function), and amyloid accumulation measured by PET imaging (brain pathology) [55]. It is notable that CD33 is expressed selectively in microglia in AD brain tissue [115], is a modulator of microglial activation, and also constitutes a druggable target that has been investigated in acute myeloid leukemia and very recently in AD [116]. Another example, discussed in Section 3.3.7, used GWAS to discover a novel association of the pro-apoptotic gene FASTKD2 with better episodic memory performance and subsequently related the memory-associated SNP to lower FASTKD2 mRNA expression (transcript), lower CSF levels of fas-mediated apoptotic factors (protein), and higher hippocampal volume and grey matter density (brain structure) [80].…”
Section: Discussionmentioning
confidence: 99%